Economic growth and structure: selected essays - Kuznets, Simon (New Delhi, 1965)
THE ESSAYS in this volume were written over the last twelve years as a by-product of quantitative analysis of the modern economic growth of nations. These papers, and the data on which they are based, draw comparisons over a wide geographic area and a long time span. Unlike the nine papers published in Economic Development and Cultural Change, those assembled here, with few exceptions, do not include the relevant statistical evidence; rather they are essays on larger themes. They either unfold a broad preliminary view-as does the first essay, "Toward a Theory of Economic Growth-or deal with the general implications of one aspect of the complex process of modern economic growth.
Keywords: Economic development- Underdeveloped countries